Determining the Influence of Employee Performance Through Organizing Citizenship Behavior by Analyzing Competency and Compensation - Candana, Dori Mittra; Putra, Rio Andhika; Afuan, M.; Purwasih, Ratih; Dharma, Robby (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
This study aimed to determine the effect of competency and compensation on employee performance through organizing citizenship behavior as an intervening variable at the Bukittinggi Regional Financial Agency. This study's population were all Bukittinggi Regional Finance Agency employees. Meanwhile, the samples were taken from 86 members (all employees of the Bukittinggi Regional Finance Agency) using quantitative techniques. The method of collecting data is through surveys and distributing questionnaires to the public as respondents. Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS) is the data analysis technique used. The results obtained were based on the Competency Hypothesis Test. There is a positive and significant influence on organizational citizenship behavior at the Bukittinggi City Financial Agency. While the Compensation variable has a positive and significant influence on Organizational Citizenship Behavior at the Bukittinggi City Financial Agency. Meanwhile, Competency positively and significantly affects employee performance at the Bukittinggi City Financial Agency.